2017
DOI: 10.1016/j.jvb.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the trait basis of career adaptability: A two-wave mediation analysis among Chinese university students

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 62 publications
(140 reference statements)
4
63
0
2
Order By: Relevance
“…It was found that proactive personality and social support has a positive significant relationship and correlation with career adaptability. This result is supported by previous researches (Cai et al, 2015;Creed et al, 2009;Ebenehi et al, 2016;Guan et al, 2017;Hirschi, 2009;Işik, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It was found that proactive personality and social support has a positive significant relationship and correlation with career adaptability. This result is supported by previous researches (Cai et al, 2015;Creed et al, 2009;Ebenehi et al, 2016;Guan et al, 2017;Hirschi, 2009;Işik, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, career adaptability has been researched to be positively related with proactive personality (Cai et al, 2015;Guan et al, 2017Guan et al, , 2015 and Social support (Creed, Fallon, & Hood, 2009;Ebenehi et al, 2016; Ute-Christine Klehe, Jelena Zikic, Annelies E. M. van Vianen, 2015).…”
Section: Literature Review Career Adaptabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…To be specific, three criteria were used to test the mediation effect: (i) the effect of independent variable (previous knowledge) on mediators (perceived vulnerability, perceived severity, response efficacy_ general, response efficacy_ ski, response cost, and self‐efficacy) should be statistically significant; (ii) mediators affect dependent variable (behaviour intention), controlling independent variable (previous knowledge); (iii) the indirect effect through mediators should be significant in the bootstrapping test. Test based on these three criteria was proved to be valid in previous studies (e.g., Guan et al, ). We firstly conducted hierarchical regression analysis to examine the first two criteria, then we used PROCESS procedures in SPSS to examine the third criteria.…”
Section: Resultsmentioning
confidence: 73%